Konsep, Implementasi, dan Aktualisasi Nilai-Nilai Akhlak Karimah di Sekolah Menengah Atas - Ma'muroh, Ma'muroh; Edidarmo, Toto (Perkumpulan Alumni dan Santri Mahyajatul Qurro’, 2022)
High school (SMA), as the most crucial education in shaping the character of its students, has doubted its effectiveness. Discriminatory cases that occur are one of the roots. Several studies suggest the necessity of inculcating Islamic educational values ​​through Islamic religious education subjects. As a result, assessment management and learning implementation are essential. This research explores more deeply to strengthen the concept, implementation, and actualization of karimah moral values in high school. The research was conducted at SMAN 6 South Tangerang using a qualitative descriptive approach. The data in this research are the results of interviews with stakeholders of SMAN 6 South Tangerang, documentation, and questionnaires to students. The results showed that the concept, implementation, and actualization of the moral values ​​of karimah at SMAN 6 South Tangerang were embodied in school programs and manifested in exemplary attitudes by Islamic Religious Education teachers. In addition, students' perceptions of Islamic Religious Education subjects align with the values ​​of Akhlak Karimah that they do. In conclusion, the program for implementing karimah and religious moral values ​​at SMAN 6 South Tangerang can be used as a model to strengthen the concept, implementation, and actualization of karimah moral values ​​in senior high schools in Indonesia.